2017
DOI: 10.5455/umj.20171108031208
|View full text |Cite
|
Sign up to set email alerts
|

The Regenerative Effects of Hemostatic Plant Extract in Second Degree Burn Wound

Abstract: This is an Open Access article distributed under the terms of Creative Commons Attribution Non-Commercial License which permits unrestricted non-commercial use, distribution, and reproduction in any area, original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…17 The results of another rat study demonstrated that ABS had a positive effect on second degree thermal burn healing. 18 Aktas et al 19 explained the mechanism of due to ABS. In their study, ABS increased the number of cells anchoring the important markers of soft tissue healing such as collagen type 1, collagen type 3, a-smooth muscle actin, fibronectin, b-2 microglobulin, vascular endothelial growth factor, cyclooxygenase-2 and mononuclear phagocyte marker.…”
Section: Discussionmentioning
confidence: 99%
“…17 The results of another rat study demonstrated that ABS had a positive effect on second degree thermal burn healing. 18 Aktas et al 19 explained the mechanism of due to ABS. In their study, ABS increased the number of cells anchoring the important markers of soft tissue healing such as collagen type 1, collagen type 3, a-smooth muscle actin, fibronectin, b-2 microglobulin, vascular endothelial growth factor, cyclooxygenase-2 and mononuclear phagocyte marker.…”
Section: Discussionmentioning
confidence: 99%
“…The burns were induced in Wistar albino rats by Kaya et al [ 4 ] they showed that ABS decreases the inflammation and wound diameters and increases the wound contraction and tissue fibrosis in rats with burn injuries. The results of another rat study demonstrated that ABS has a positive effect on second-degree thermal burn healing [ 6 ].…”
Section: To the Editormentioning
confidence: 99%